Decyzja ustalająca wymiar kary biegnącej jako element procedury nałożenia administracyjnej kary pieniężnej. Glosa do wyroku Naczelnego Sądu Administracyjnego z dnia 19 października 2021 r., III OSK 4119/21 - Wincenciak, Mirosław (PRAWO i WIĘŹ, 2025)
The decision establishing the amount of the current penalty specifies the date from which the current penalty will be calculated, as well as the penalty rate. Therefore, the penalty rate, according to Article 300 of the Environmental Protection Act, is reduced to determining the penalty rate. The penalty rate is one element of the procedure for imposing an administrative fine.